Analysis of the Effects of Variation of Phantom Diameter on Radiation Dose on Image Dicom CT Scan Using IndoseCT - Andriani, Intan; Budiwati, Trisna; Ningtias, Diah Rahayu (Sean Institute, 2022)
CT-Scan is one of the imaging modalities in the field of radiodiagnostics that can produce axial, coronal, and sagittal slices of the object or patient performing the examination. CT-Scan can be applied to diagnose trauma in cancer cases. The use of CT-Scan aircraft certainly provides a fairly large radiation dose compared to other diagnostic imaging modalities (Bushberg, 2012). This study aimed to determine the effect of the thickness (diameter) of the object on the radiation dose. This study's benefit is providing accuracy in receiving the body's absorbed dose on CT-Scan examination. This research is experimental. The study used a sample of 5 phantoms with variations in the diameter of 8 cm, 16 cm, 24 cm, 32 cm, and 40 cm. The data is obtained from the phantom scan results, which are inputted into the IndoseCT program. The data generated by IndoseCT will be analyzed regarding the amount of radiation dose received by each phantom size. The final result expected from this research is the evaluation of measurement or monitoring of doses to patients who can support radiation protection programs in ensuring patient safety.